Salafi’s Da’wah and the Phenomenon of Religious Piety among Hijrah Artists - Ahmad Zaenuri; Habibie Yusuf (Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
In the last decade, along with the huge social media, religious piety among national celebrities has increased dramatically. This trend is characterized by the emergence of a number of artists with traditional Islamic-Salafi fashion community. Trousers above the ankle, bushy beards, thin mustaches, women's veils and the common term of akhi and ukhti, as well as many other anomalies. Salafi da’wa is, on the one hand, a condensed way of da’wa (not much by fiqh logic). His opinions concentrated more on the actual understanding of the Quran and the Sunnah. But, on the other hand, a lot of artists who are typically middle-class, educated and rationalist suit the community. This article seeks to address the question of why the phenomenon of religious piety of artists is more in line with the trend of the Salafi communities? Phenomenological descriptive methodology is the analysis tool used. To address the above question, the author presents the paradigm of Benford and Snow da’wa. The results of this study reveal that the Salaf da’wa was able to frame its da'wah concepts in accordance with reason, Islamic, modern standards, and to respond to the demands of the Ummah in such a way that many artists followed.